Mining the Web of Science for African cities and climate change (1991–2021) - Mhedhbi, Zohra; Mazzega, Pierre; Gaston, Méhéret; Haouès-Jouve, Sinda; Hidalgo, Julia (Frontiers in Sustainable Cities, 2023)
This study provides a synthetic overview of thirty years of research devoted to urban climate change in Africa. Which cities in Africa are being researched on the impacts of climate change affecting them? What are the main social and urban issues and how are they linked? Is the development of climate services envisaged for these cities? Related to which local issues? Some answers are drawn by text mining the metadata of more than a thousand articles published in the 1991-2021 period and recorded in the Web of Science. The evidences produced are based on the design and exploitation of a taxonomy of keywords forming a set of issues and on their articulation in a network based on their co-occurrences in the articles’ metadata. Forty-eight African countries and 134 cities are cited, Cairo, Dar es Salaam, Cape Town, Accra, Lagos, Durban, Nairobi, Addis Ababa, Kampala and Johannesburg being the cities deferring the largest number of studies. The salient urban climate change issues - health, water, energy, social issues and governance, followed by agriculture and food, mitigation, heat, urban territories, risks and hazards - are generally addressed in their interdependences. Urbanization and the implementation of associated policies, as well as the management of water resources, floods health and energy, and land use and land cover changes to a less extent, are proving to be the most pressing challenges. In view of the intricacy of these issues, climate services appear underdeveloped in African cities and barely confined to the acquisition and modelling of environmental data for decision-making in adaptation planning.